2013
DOI: 10.1155/2013/378219
|View full text |Cite
|
Sign up to set email alerts
|

Total Glucosides of Paeony Capsule Plus Compound Glycyrrhizin Tablets for the Treatment of Severe Alopecia Areata in Children: A Randomized Controlled Trial

Abstract: Total glucosides of paeony capsule (TGPC) and compound glycyrrhizin tablets (CGT) are plant extracts of glycosides. We conducted this study to examine the efficacy and safety of TGPC plus CGT for severe alopecia areata in children. 117 subjects were randomly allocated into TGPC plus CGT group or CGT group. For consecutive 12 months, subjects were given oral TGPC and CGT or oral CGT alone. The outcome measures included score of alopecia areata severity, effective rate, and adverse events observed in the 3rd, 6t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
(11 reference statements)
3
22
0
Order By: Relevance
“…TGP were recently reported to induce regulatory CD4 + CD25 + T cells by increasing Foxp3 demethylation , and inhibit dendritic cells maturation by arresting signaling pathways triggered by toll‐like receptors 4 and 5 . Recently, there was a study found that TGP capsule plus compound glycyrrhizin tablets appeared effective and safe for severe alopecia areata in children . The present study has demonstrated the potential of TGP for treating immune‐related diseases by ameliorating inflammation in therapy.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…TGP were recently reported to induce regulatory CD4 + CD25 + T cells by increasing Foxp3 demethylation , and inhibit dendritic cells maturation by arresting signaling pathways triggered by toll‐like receptors 4 and 5 . Recently, there was a study found that TGP capsule plus compound glycyrrhizin tablets appeared effective and safe for severe alopecia areata in children . The present study has demonstrated the potential of TGP for treating immune‐related diseases by ameliorating inflammation in therapy.…”
Section: Discussionsupporting
confidence: 58%
“…Recently, there was a study found that TGP capsule plus compound glycyrrhizin tablets appeared effective and safe for severe alopecia areata in children (15). The present study has demonstrated the potential of TGP for treating immune-related diseases by ameliorating inflammation in therapy.…”
Section: (B) Features Include Epithelioid Macrophages With Foreign Bosupporting
confidence: 62%
“…Its expression was significantly increased in a variety of skin diseases, such as psoriasis, alopecia areata, vitiligo, atopic dermatitis, Henoch‐Schönlein purpura (HSP), pemphigus, and drug‐induced hypersensitivity syndrome/drug reaction with eosinophilia and systemic symptoms (DRESS) . Due to the similar pharmacological efficacy to corticosteroids but with milder side effects, Glycyrrhizin has been widely utilized in several dermatologic disorders for many years, such as active‐stage generalized vitiligo, psoriasis, alopecia areata, and is also reported to be effective in alleviating the symptoms of atopic dermatitis and systemic sclerosis in animal model . Based on the clinical observation that patients with recalcitrant Riehl’s melanosis may present with facial erythema and itching, which are signs of local inflammation, we applied Glycyrrhizin compound 75 mg orally three times a day for all enrolled patients, aiming to alleviate the inflammatory reaction.…”
Section: Discussionmentioning
confidence: 99%
“…In a RCT comparing the therapeutic effects of TGPC and glycyrrhizin, both were found to be markedly effective . Another RCT comparing the combination of TGPC and glycyrrhizin to glycyrrhizin monotherapy showed that combination therapy resulted in more hair growth . No molecular or PCT studies characterizing these two plant extracts were available.…”
Section: Second‐line Therapiesmentioning
confidence: 99%